Forecasting U.S. Industrial Production : Does the Baltic Dry Index provide additional predicting power - Määttä, Oskari (My University, 2020)
Various economic leading indicators are continuously referred in the financial discussion. Asset managers, central bankers and trading participants pay attention to myriads leading indicators and base their decisions on the information of the expected economic performance. This study investigates the relationship between leading indices and US industrial output and aims to provide further knowledge by evaluating the forecast accuracy of leading indices. Furthermore, the capabilities of Baltic Dry Index as a leading indicator is evaluated alongside with asserting momentum’s usefulness to enhance forecasting accuracy. Recursive expanding estimation window forecasts were created for US industrial production. Forecasts are based on the on the estimated time series of Conference Boards Leading Index, Baltic Dry Index, US government bond yield spread and the autocorrelation of the of the dependent variable. Robust empirical analysis concluded that Baltic Dry Index does not have predictive nature for US industrial production. In addition, momentum enhances the forecasting performance of Conference Board Leading Index when autocorrelation variable was included in the forecasting model with the Leading Index to predict the US industrial output. These results suggest that Baltic Dry Index should not be considered as a leading indicator and Conference Boards Leading Index should not include it as a constituent. However, momentum in a for of autocorrelation should be considered within the Conference Boards Leading Index as it enhances its forecasting accuracy.

Taloudellisia indikaattoreita seurataan taloudellisessa keskustelussa jatkuvasti. Varainhoitajat, keskuspankkiirit ja kaupankäyntiosapuolet huomioivat taloudellisten indikaattorien tuomaa informaatiota tehdäkseen päätöksiä tulevaisuuden todennäköisen taloudellisen tilan perusteella. Tämä tutkimus käsittelee Yhdysvaltojen teollisuustuotannon ja johtavien taloudellisten indikaattorien välistä suhdetta tarkoituksenaan löytää informaatiota indikaattorien selitysvoimasta. Lisäksi arvioidaan Baltic Dry Indexin käyttökelpoisuutta johtavana indikaattorina sekä momentumin hyödyntämistä johtavien indeksien ennusteissa. Yhdysvaltojen teollisuustuotannolle luotiin rekursiivisia ennusteita, jotka hyödyntävät ekspansiivista estimointi-ikkunaa. Ennustemallien estimaatit perustuvat Conference Board Leading Indexiin, Baltic Dry Indexiin, Yhdysvaltojen valtiovelkakirjojen korkojen väliseen eroon sekä selitettävän muuttujan autokorrelaatioon. Robustin analyysin perusteella Baltic Dry Index ei sisällä ennustevoimaa Yhdysvaltojen teollisuustuotannolle. Lisäksi momentumin lisääminen ennustemalliin tarkensi ennustemalleja merkittävästi, kun Yhdysvaltojen teollisuustuotantoa selittävinä muuttujina olivat autokorrelaatio ja Conference Board Leading Index. Näiden tulosten perusteella Baltic Dry Index ei ole johtava taloudellinen indikaattori ja sitä ei tulisi lisätä Conference Board Leading Index komponentiksi. Sen sijaan momentum tulisi huomioida Conference Board Leading Indexissä, koska sen lisääminen ennustemalliin tarkentaa ennustetta merkittävästi.
Keywords: Leading Indicators, Forecasting